The -2518 A/G single nucleotide polymorphism of MCP-1 in myelofibrosis: functional characterization on ex-vivo patient cells - Pozzi, Giulia; Masselli, Elena; Carubbi, Cecilia; Gobbi, Giuliana; Galli, Daniela; Mirandola, Prisco; Micheloni, Cristina; Arcari, Maria Luisa; Aversa, Franco; Vitale, Marco (Italian Journal of Anatomy and Embryology, 2018)
Host genetic variations have an essential role in the mutational landscape of Philadelphia-negative MPN [1,2]. However, the contribution of inherited factors in disease phenotype and evolution is poorly charac- terized. In MPNs, chronic inflammation triggers neoplastic transformation and catalyzes clonal evolution toward end-stage disease [3]. We recently demonstrated that the -2518 A/G SNP of the Monocyte Chemoat- tractant Protein-1 (MCP-1, rs1024611) is an inherited host genetic factor associated with secondary myelofi- brosis (sMF) and a biomarker of disease severity in MF [4]. Here we aimed to characterize MCP-1 expression in MF according to patients’ genotype, and the potential cellular source(s) of this chemokine. For this study, 15 therapy-naïve MF patients were recruited, 4 healthy subjects and 4 apheresis bags were utilized as con- trols (CTRL). MF were stratified according to their rs1024611 genotype in A/A (wild type), A/G and G/G (polymorphic). Peripheral blood mononuclear cells (MNCs) were isolated by Ficoll-Hypaque gradient, in part pelleted (resting, T0) and in part seeded in RPMI-1640 medium with 1.1 ng/ml of IL-1 β for 20 hrs (T1). T0 and T1 cells were processed for RNA extraction. CD34+-cells were purified from MF peripheral blood and from apheresis bags by immunomagnetic selection and differentiated toward the MK lineage as previously described [5]. Mature CD41+ MKs were then processed for RNA extraction. MCP-1 expression was evaluat- ed by real-time PCR. We demonstrated that MF-MNCs significantly over-expressed MCP-1 as compared to CTRL-MNCs at basal state. Upon IL1β stimulation, we observed a dose-dependent effect of the -2518 A/G SNP on MCP-1 expression, with polymorphic patients displaying a >100-times higher fold-increase (T1 vs. T0) in MCP-1 levels as compared to A/A. MF-MKs also showed a significantly higher expression of MCP-1 as compared to CTRL. Finally, MF-CD34+-cells from A/G+G/G patients displayed impaired MK differentiation compared to A/A, as indicated by a significantly lower number of CD41+-cells obtained in culture. Our data show that circulating MNCs and CD34+-derived MKs are a major source of MCP-1 in MF. Polymorphic MF patients, who cluster with adverse hematologic characteristics, display here a higher capacity to over-express MCP-1 under an inflammatory stimulus and an impaired megakaryocytic differentiation potential. Further studies to better define the role of MCP-1 on CD34+-cells differentiation in the context of MF are desirable.